Manajemen Penggunaan Media Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah 57 Medan - Wildan; Munawir Pasaribu (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
Education is a very important medium in developing society, so that it has competence for the nation in this modern era. The purpose of this research is to determine the planning, implementation, application and evaluation of learning outcomes at SMP Muhammadiyah 57 Medan. This research uses qualitative research methods with the aim of collecting data and information according to what is available in the field in order to find out how the system is used in managing learning media in the school. This research involved teachers and 40 students from SMP Muhammadiyah 57 Medan. In searching for information using observation and interviews, while in testing the validity of the data researchers use triangulation, namely using sources, methods and time. The learning media applied shows that the results obtained can facilitate the learning process and have met good criteria and achievements in the form of increasing student motivation, maintaining interaction between teachers and students, as well as more effective use of time.